Photo reference Abbas Bin Ali (A) In the poetry of Thirteenth and Fourteenth centuries of migration - Lafta, Maitham Mohamed; Rasan, Fatima Karim (Al-Adab Journal, 2022)
The poets of the thirteenth and fourteenth centuries of immigration followed the path of the ancient poets, in terms of their use of poetic images of all kinds, the poets' reference was based on graphic images, which dominated in those two eras, as well as the emergence of other patterns during their poems, the poetic image of the references that he adopts The poets in constructing their texts, because of the characteristic of influencing the recipient, and this is what the research monitors with the Iraqi poetic production, which reveals the image of our master Al-Abbas (A) in this research, as well as the motive behind this employment, in two eras dominated by graphic images, so the poets sought the help of Several types of poetic images, in order to show their texts in an aesthetic way, as well as bringing the image closer and giving it realism.